Lithium battery negative electrode slurry and preparation method thereof
By adding polyvinyl alcohol and gelatin to the preparation of the negative electrode slurry of lithium battery, the coating peeling and cracking caused by the slurry during drying is solved, and the performance of lithium battery is significantly improved.
Patent Information
- Application Number
- CN202411570777.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
The negative electrode slurry of lithium battery is prone to cause coating peeling and cracking during drying, affecting the processing performance, production efficiency and cycle life of the battery.
By adding polyvinyl alcohol and gelatin when preparing the negative electrode slurry, the connecting force between the particles and the viscosity and elasticity of the slurry are enhanced, and the influence of capillary force is reduced, thereby improving the peel strength.
The peeling strength of the negative electrode slurry of lithium battery is improved, the coating cracking phenomenon is reduced, and the charging and discharging efficiency and cycle life of lithium battery is improved.
Smart Images

Figure CN119400869A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a negative electrode slurry for a lithium battery and a preparation method thereof. Background Art
[0002] Lithium batteries are widely used in many fields due to their high energy density, long cycle life, low self-discharge, and environmental protection. The production process of lithium battery pole pieces is an important part of the entire lithium battery manufacturing process, mainly including slurry preparation, coating, etc. The quality of the slurry directly affects the performance of the lithium battery produced.
[0003] The negative electrode slurry of lithium batteries is mainly composed of adhesives, conductive agents, active materials and solvents. The preparation of negative electrode slurry includes a series of process steps such as mixing, dissolving and dispersing solid and liquid materials. The effective combination of particles in the slurry is crucial. Excessive dispersion can easily cause the peeling of electrode materials and cracking of the electrode surface, thus affecting the processing performance, production efficiency and yield of the battery, and greatly shortening the cycle life of the battery.
[0004] The invention patent with the authorization announcement number CN 114927679 B discloses a lithium battery negative electrode slurry and its preparation method. The lithium battery negative electrode slurry includes a solvent, a binder and a powder. The powder includes the following components by weight: 35-45 parts of graphite, 53-55 parts of silicon negative electrode, 0.18-0.4 parts of conductive agent, 0.22-0.6 parts of single-walled carbon nanotubes, and 1.0-1.8 parts of sodium carboxymethyl cellulose; the solvent includes deionized water and N-methylpyrrolidone. The handling and drying of N-methylpyrrolidone in the battery manufacturing process is a key factor. If N-methylpyrrolidone is not completely removed from the pole piece, the residual N-methylpyrrolidone may affect the performance of the electrolyte, and then affect the battery's charge and discharge efficiency and cycle life and other battery performance. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a lithium battery negative electrode slurry and a preparation method thereof, and the prepared negative electrode slurry has high peeling strength.
[0006] The technical solution of the present invention to solve the above problems is as follows:
[0007] A method for preparing a negative electrode slurry for a lithium battery comprises the following steps:
[0008] S1, mixing graphite and conductive agent uniformly to obtain a dry mixture;
[0009] S2, mixing the dry blend with sodium carboxymethyl cellulose glue, aqueous glue and deionized water, stirring and dispersing under a vacuum degree of ≤-85Kpa to obtain a primary slurry;
[0010] S3, the primary slurry is mixed evenly with water-based glue and deionized water, and stirred and dispersed under a vacuum degree of ≤-85Kpa to obtain a secondary slurry;
[0011] S4, under a vacuum degree of ≤-85Kpa, add deionized water, additives, and styrene-butadiene rubber to the secondary slurry, stir and disperse, and obtain a negative electrode slurry;
[0012] The additive is selected from at least one of polyvinyl alcohol and gelatin.
[0013] The negative electrode slurry of lithium batteries is an unstable suspension. After the negative electrode slurry is coated, when the wet coating containing suspended particles dries, all the particles are suspended in the solvent at the beginning. As the solvent evaporates, the gas-liquid interface reaches the coating surface during the drying process, and the air-solvent interface between the particles generates capillary force. At this time, the particles are subjected to the compression force perpendicular to the gas-liquid interface generated by the capillary force. With further drying, the gas-liquid interface enters the interior of the coating, and the capillary force increases with the evaporation of the solvent, thereby exerting further compression force on the particles, resulting in a lower peeling force of the coating, causing the coating to crack.
[0014] After adding polyvinyl alcohol and gelatin, polyvinyl alcohol can form hydrogen bonds with water, increasing the connection between particles, thereby improving the peeling strength and reducing the possibility of cracking; gelatin molecules form a three-dimensional network structure in the slurry, which increases the viscosity and elasticity of the slurry, reduces the influence of capillary forces, improves the peeling strength, and thus reduces the phenomenon of coating cracking. In addition, since there are a large number of carboxyl groups, amino groups and hydroxyl groups on the gelatin molecular chain, they can form hydrogen bonds with the hydroxyl groups in the polyvinyl alcohol molecules, further enhancing the adhesion and stability of the negative electrode slurry, thereby improving the peeling strength.
[0015] Preferably, the conductive agent is selected from one or more of conductive carbon black, graphene, and carbon nanotubes.
[0016] Preferably, the mass ratio of the graphite, the conductive agent and the sodium carboxymethyl cellulose glue is (94-97):(0.5-2):(14-23), and the solid content of the sodium carboxymethyl cellulose glue is 1.5-2.5%.
[0017] Preferably, the aqueous glue is a PAA solution with a solid content of 15-25%.
[0018] Preferably, the mass ratio of the graphite, the conductive agent and the aqueous glue is (94-97):(0.5-2):(8-15).
[0019] Preferably, in step S2, the mass ratio of sodium carboxymethyl cellulose glue, aqueous glue and deionized water is (95-110):(25-35):(50-70), the solid content of the sodium carboxymethyl cellulose glue is 1.5-2.5%, and the solid content of the aqueous glue is 15-25%.
[0020] Preferably, in step S3, the mass ratio of the water-based glue to deionized water is (25-35):(80-95), and the solid content of the water-based glue is 15-25%.
[0021] Preferably, the mass of the additive is 0.0001 to 20% of the total mass of solid matter in the negative electrode slurry.
[0022] Preferably, the mass ratio of polyvinyl alcohol to gelatin is (0.01-1):(0.01-1).
[0023] Preferably, in step S4, the mass ratio of deionized water to styrene-butadiene rubber is (140-160):(3-9).
[0024] Preferably, in step S1, the graphite and the conductive agent are stirred at 30-50° C., at 15-25 rpm, and dispersed at 490-510 rpm for a total of 50-70 min to obtain a dry mixture.
[0025] Preferably, in step S2, the dry mix is stirred with sodium carboxymethyl cellulose glue, aqueous glue and deionized water at 25 to 35 rpm for 10 to 20 min at 30 to 50° C. After completion, the mixture is stirred at 25 to 35 rpm and dispersed at 480 to 520 rpm for a total of 80 to 100 min at a vacuum degree ≤-85 Kpa and 30 to 50° C. to obtain a primary slurry.
[0026] Preferably, in step S3, at 30-50°C, the primary slurry is stirred with aqueous glue and deionized water at 20-30rpm and dispersed at 480-520rpm for 5-15min. After completion, the mixture is stirred at 25-35rpm and dispersed at 1150-1250rpm for a total of 110-130min at a vacuum degree ≤-85Kpa and 30-50°C to obtain a secondary slurry.
[0027] Preferably, in step S4, at 30-50° C. and a vacuum degree ≤-85 Kpa, deionized water and additives are added to the secondary slurry, the mixture is stirred at 25-35 rpm and dispersed at 1050-1150 rpm for a total of 55-65 min, the viscosity of the slurry is tested, the viscosity of the slurry is adjusted, styrene-butadiene rubber is added, the mixture is stirred at 20-30 rpm and dispersed at 600-700 rpm for a total of 25-35 min, the vacuum is broken, and the negative electrode slurry is obtained.
[0028] The present invention also provides a lithium battery negative electrode slurry prepared by the above preparation method.
[0029] The present invention has the following beneficial effects:
[0030] In the present invention, polyvinyl alcohol and / or gelatin are added when preparing the negative electrode slurry. Polyvinyl alcohol can form hydrogen bonds with water to increase the connection force between particles in the slurry. Gelatin molecules form a three-dimensional network structure in the slurry, which improves the viscosity and elasticity of the slurry and reduces the influence of capillary force. In addition, the carboxyl group, amino group and hydroxyl group on the gelatin molecular chain can form hydrogen bonds with the hydroxyl group in the polyvinyl alcohol molecules, further enhancing the adhesion and stability of the negative electrode slurry, thereby improving the peel strength of the slurry, avoiding the phenomenon of coating cracking, and further improving the charge and discharge efficiency and cycle life of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The capacity retention rate diagram of the lithium batteries of Examples 2 and 3;
[0032] Figure 2 This is a picture of the slurry before adjusting the viscosity in step S4 of Example 1. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0034] Example 1
[0035] Preparation of sodium carboxymethyl cellulose (CMC) glue:
[0036] Add 2.02 kg of CMC to 59 kg of deionized water, stir at 20 rpm for 5 min and disperse at 500 rpm for 10 min at 20-35 ° C, then add 39.59 kg of deionized water, stir at 20 rpm for 100 min and disperse at 1000 rpm for 140 min at a vacuum degree of ≤-85 Kpa at 20-35 ° C to obtain a CMC glue with a solid content of 1.8-2.2% and a viscosity of 3000-15000 Mpa·s.
[0037] Preparation of negative electrode slurry:
[0038] S1. At 30-50°C, 483 kg of graphite and 5.06 kg of conductive carbon black were stirred at 20 rpm for 20 min and dispersed at 500 rpm for 40 min to obtain a dry blend;
[0039] S2. At 30-50°C, add 101kg CMC glue, 31.6kg PAA solution (solid content is 20%) and 59kg deionized water to the dry mix, perform the first kneading, stir at 30rpm for 15min, perform the first scraping after the stirring is completed, and after completion, stir at 30rpm for 35min and disperse at 500rpm for 55min at a vacuum degree of ≤-85Kpa and 30-50°C to obtain a primary slurry with a solid content of 73%;
[0040] S3, at 30-50°C, add 31.6kg PAA solution (solid content is 20%) and 86kg deionized water to the primary slurry, perform a second kneading, stir at 25rpm for 6min, disperse at 500rpm for 4min, perform a second scraping after the stirring is completed, and then, at a vacuum degree of ≤-85Kpa and 30-50°C, stir at 30rpm for 50min and disperse at 1200rpm for 70min to obtain a secondary slurry with a solid content of 63%;
[0041] S4, vacuum degree ≤ -85Kpa, at 30-50℃, add 150kg deionized water and 0.51kg polyvinyl alcohol and gelatin (the mass ratio of polyvinyl alcohol to gelatin is 7:3) to the secondary slurry, stir at 30rpm for 25min, disperse at 1100rpm for 35min, the solid content is about 53%, and the slurry is a black liquid. Figure 2 As shown; Take a small sample to test the viscosity of the slurry, and the measured viscosity value is 3900Mpa·s. Add 10kg of deionized water and disperse at 1100rpm for 30min to adjust the viscosity of the slurry to about 3500Mpa·s. Then add 6.3kg of styrene-butadiene rubber (SBR), stir at 25rpm for 10min, and disperse at 650rpm for 20min. At this time, the solid content of the slurry is maintained at about 53%, break the vacuum, and obtain the negative electrode slurry. The obtained negative electrode slurry has good fluidity, no obvious large particles, and a particle size of ≤30μm. The viscosity rises slowly after 72h of static standing, and the difference in solid content between the upper and lower layers does not exceed 2%. The above negative electrode slurry should be used up within 48h.
[0042] The obtained negative electrode slurry was coated on copper foil to prepare a negative electrode sheet, and the coating conveying speed was 50 m / min.
[0043] Example 2
[0044] Compared with Example 1, the preparation method is different in that 1.52 kg of polyvinyl alcohol and gelatin (the mass ratio of polyvinyl alcohol to gelatin is 7:3) are added to S4.
[0045] Example 3
[0046] Compared with Example 1, the preparation method is different in that 3.04 kg of polyvinyl alcohol and gelatin (the mass ratio of polyvinyl alcohol to gelatin is 7:3) are added to S4.
[0047] Example 4
[0048] Compared with Example 1, the preparation method is different in that 5.1 kg of polyvinyl alcohol and gelatin (the mass ratio of polyvinyl alcohol to gelatin is 7:3) are added to S4.
[0049] Example 5
[0050] Compared with Example 1, the preparation method is different in that 6.1 kg of polyvinyl alcohol and gelatin (the mass ratio of polyvinyl alcohol to gelatin is 7:3) are added to S4.
[0051] Comparative Example 1
[0052] Compared with Example 1, the preparation method is different in that polyvinyl alcohol and gelatin are not added to S4; the coating conveying speed is 25 m / min.
[0053] Comparative Example 2
[0054] Compared with Example 1, the preparation method is different in that 0.51 kg of polyvinyl alcohol and gelatin are replaced by 5.1 kg of ethylene carbonate in S4.
[0055] Comparative Example 3
[0056] Compared with Example 1, the preparation method is different in that 0.51 kg of polyvinyl alcohol and gelatin are replaced by 5.1 kg of N-methylpyrrolidone in S4.
[0057] The performance tests were performed on the pole pieces of the above-mentioned embodiments 1 to 5 and comparative examples 1 to 3, and the results are shown in Table 2.
[0058] Peel strength test method: Cut the negative electrode sheet into a specification of 400mm in length and 25mm in width, take a steel plate with a length of 200mm and a width of 50mm, tightly fit the double-sided tape with a width of 25mm on the center of the steel plate, peel off the double-sided tape, fit the electrode sheet on the double-sided tape, insert the steel plate with the electrode sheet fixed on it into the lower clamp of the tensile testing machine, and fix it vertically; insert the un-adhesive electrode sheet into the upper clamp of the tensile testing machine and fix it, so that the electrode sheet attached to the double-sided tape is 180° with the electrode sheet fixed by the upper clamp, the electrode sheet peeling length is 100mm, and the peeling speed is 75mm / min.
[0059] Table 1: Preparation parameter table of Examples 1 to 5 and Comparative Examples 1 to 3
[0060] Coating oven temperature (ten sections) (℃) additive Example 1 85 / 95 / 100 / 108 / 109 / 106 / 100 / 95 / 92 / 80 0.1% polyvinyl alcohol and gelatin Example 2 85 / 95 / 100 / 108 / 109 / 106 / 100 / 95 / 92 / 80 0.3% polyvinyl alcohol and gelatin Example 3 85 / 95 / 100 / 115 / 118 / 118 / 100 / 95 / 92 / 80 0.6% polyvinyl alcohol and gelatin Example 4 85 / 98 / 105 / 118 / 122 / 122 / 107 / 98 / 92 / 80 1.0% Polyvinyl alcohol and gelatin Example 5 85 / 98 / 105 / 118 / 122 / 122 / 107 / 98 / 92 / 80 1.2% Polyvinyl alcohol and gelatin Comparative Example 1 65 / 75 / 80 / 80 / 85 / 85 / 80 / 75 / 65 / 50 none Comparative Example 2 80 / 85 / 90 / 95 / 100 / 100 / 95 / 90 / 80 / 75 1% Ethylene carbonate Comparative Example 3 80 / 85 / 90 / 95 / 100 / 100 / 95 / 90 / 80 / 75 1% N-methylpyrrolidone
[0061] Table 2: Table of pole piece performance test of Examples 1 to 5 and Comparative Examples 1 to 3
[0062]
[0063] According to Tables 1 and 2, compared with the case where no additives are added in Comparative Example 1, after adding polyvinyl alcohol and gelatin in Examples 1 to 5, the peel strength is not less than 8.5 N / m, and there are no obvious cracks in the pole piece. Therefore, the addition of polyvinyl alcohol and gelatin can improve the peel strength of the pole piece;
[0064] It can be seen from Tables 1 and 2 that the residual rates of additives in Examples 1 to 5 are all lower than those in Comparative Examples 2 and 3, and the peel strengths in Examples 1 to 5 are also better than those in Comparative Examples 2 and 3, indicating that compared with using ethylene carbonate and N-methylpyrrolidone, using polyvinyl alcohol and gelatin as additives can reduce the residual rate of additives and improve the peel strength of the electrode.
[0065] The pole pieces in the above-mentioned embodiments and comparative examples were made into lithium-ion batteries, and their performance was tested. The test results are shown in Table 3.
[0066] Test method:
[0067] Initial charge and discharge efficiency: 0.5c constant current and constant voltage charging, 0.5c constant current discharge, formation temperature 45°C, split capacity ambient temperature 25±3°C. Initial charge and discharge efficiency = initial discharge capacity / (formation charge capacity + split capacity supplement capacity)
[0068] Capacity retention rate: At 45°C, the activated battery was cycled at 1C for 350 cycles, and the capacity retention rate at the 350th cycle was recorded.
[0069] Table 3: Performance test table of lithium batteries in Examples 1 to 5 and Comparative Examples 1 to 3
[0070] First charge and discharge efficiency (%) Capacity retention rate (45℃ cycle 350 times) Example 1 92.59 94.7 Example 2 93.34 97.3 Example 3 93.93 96.8 Example 4 93.47 96.34 Example 5 92.28 95.37 Comparative Example 1 89.12 91.2 Comparative Example 2 83.21 89.7 Comparative Example 3 82.45 87.4
[0071] According to Tables 1 to 3, it can be seen that the residual rate of additives (ethylene carbonate, N-methylpyrrolidone) in Comparative Examples 2 and 3 is relatively high, and their charge and discharge efficiency and cycle life are relatively poor. This is because the residual additives may affect the performance of the electrolyte, and thus affect the performance of the lithium battery;
[0072] It can also be seen from Tables 1 to 3 that the initial charge and discharge efficiency and capacity retention rate of Examples 1 to 5 are better than those of Comparative Examples 1 to 3, indicating that the addition of polyvinyl alcohol and gelatin can improve the charge and discharge efficiency and cycle life of lithium-ion batteries.
Claims
1. A method for preparing a negative electrode slurry for a lithium battery, characterized in that: The following steps are involved: S1, mixing graphite and conductive agent uniformly to obtain a dry mixture; S2, mixing the dry blend with sodium carboxymethyl cellulose glue, aqueous glue and deionized water, stirring and dispersing under a vacuum degree of ≤-85Kpa to obtain a primary slurry; S3, the primary slurry is mixed evenly with water-based glue and deionized water, and stirred and dispersed under a vacuum degree of ≤-85Kpa to obtain a secondary slurry; S4, under a vacuum degree of ≤-85Kpa, add deionized water, additives, and styrene-butadiene rubber to the secondary slurry, stir and disperse, and obtain a negative electrode slurry; The additive is selected from at least one of polyvinyl alcohol and gelatin.
2. The method for preparing a negative electrode slurry for a lithium battery according to claim 1, characterized in that: The mass ratio of the graphite, the conductive agent and the sodium carboxymethyl cellulose glue is (94-97):(0.5-2):(14-23), and the solid content of the sodium carboxymethyl cellulose glue is 1.5-2.5%.
3. The method for preparing a negative electrode slurry for a lithium battery according to claim 1, characterized in that: The water-based glue is a PAA solution with a solid content of 15-25%.
4. The method for preparing a negative electrode slurry for a lithium battery according to claim 3, characterized in that: The mass ratio of the graphite, the conductive agent and the aqueous glue is (94-97):(0.5-2):(8-15).
5. The method for preparing a negative electrode slurry for a lithium battery according to claim 1, characterized in that: In step S2, the mass ratio of sodium carboxymethyl cellulose glue, aqueous glue and deionized water is (95-110):(25-35):(50-70), the solid content of the sodium carboxymethyl cellulose glue is 1.5-2.5%, and the solid content of the aqueous glue is 15-25%.
6. The method for preparing a negative electrode slurry for a lithium battery according to claim 1, characterized in that: In step S3, the mass ratio of the water-based glue to deionized water is (25-35):(80-95), and the solid content of the water-based glue is 15-25%.
7. The method for preparing a negative electrode slurry for a lithium battery according to claim 1, characterized in that: The mass of the additive is 0.0001 to 20% of the total mass of the solid matter in the negative electrode slurry.
8. The method for preparing a negative electrode slurry for a lithium battery according to claim 1, characterized in that: The mass ratio of the polyvinyl alcohol to gelatin is (0.01-1):(0.01-1).
9. The method for preparing a negative electrode slurry for a lithium battery according to claim 1, characterized in that: In step S4, the mass ratio of deionized water to styrene-butadiene rubber is (140-160):(3-9).
10. A negative electrode slurry for a lithium battery prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A kind of negative electrode slurry of lithium battery and its preparation method
CN114927679B